Digital Transformation and Innovation in Islamic Education Management in Preparing the Golden Generation of Indonesia - Malkayanti S. Sangadji; Ulfi Saniah; Nur Ali; Moh Ali (Kasyafa: Jurnal Pendidikan Agama Islam, 2025)
This study aims to examine digital transformation and innovation in the management of Islamic education as strategic efforts to prepare the Indonesia's Golden Generation 2045. The research employs a literature review method by analyzing various sources related to the implementation of digital technology and managerial innovation in Islamic educational institutions. The findings indicate that digitalization of the Islamic Education Management Information System (SIMPI), the utilization of e-learning platforms, and the integration of artificial intelligence (AI) play vital roles in improving management efficiency, learning quality, and accessibility of education. Additionally, technology-based innovations that strengthen communication among stakeholders and expand educational reach especially in remote areas are essential. However, the implementation of digital transformation faces multiple challenges, such as infrastructural deficiencies, low digital literacy, and unequal access to technology in certain regions. Therefore, ongoing innovation and comprehensive strategies are required to ensure that Islamic education remains relevant, adaptive, and capable of supporting the national vision of Indonesia's Golden Generation 2045.